PERAN TRADISI DALAM TREND FORECASTING - Akbar Adhi Satrio; Tri Hasdianto Hasdianto; Amelinda Alysia A.V.K. (Serat Rupa: Journal of Design, 2020)
This study is preliminary research of "The Trend Forecasting Translation Analysis in The Context of Craft". Trend Forecasting is a developed method that aims to predict future trends through research and analysis based on factual data of phenomena that occurs during certain time frames. The process includes analyzing various factors including technological development, lifestyle, also shifts of paradigm that form strategic decisions towards product design. However, the role of the trend forecast being applied to today’s craft designing process needs to be further reviewed. It is related to the fact where traditional elements are attached to all craft products, emphasized to be well-preserved in showing its characteristics of culture and tradition. This study seeks to map where the position of tradition takes place among the trend forecasting process through the analysis of a.) field studies in institutions and practitioners in the field of trend forecast; b.) comparative study of the position of tradition in the process of trend forecasting based on three kinds of literature namely ”The Trend Forecaster’s Handbook”, ”How to Research Trends”, and ”Fashion Forecasting”. In the scope of methods, the results of this study show that tradition stands as a significant data in the process of constructing a trend forecast. However, the perspective is not under the context of local culture but as the behavior of people.